If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2x + -1(4 + -7y + 6x) + 5y) = 0 Reorder the terms: 2(2x + -1(4 + 6x + -7y) + 5y) = 0 2(2x + (4 * -1 + 6x * -1 + -7y * -1) + 5y) = 0 2(2x + (-4 + -6x + 7y) + 5y) = 0 Reorder the terms: 2(-4 + 2x + -6x + 7y + 5y) = 0 Combine like terms: 2x + -6x = -4x 2(-4 + -4x + 7y + 5y) = 0 Combine like terms: 7y + 5y = 12y 2(-4 + -4x + 12y) = 0 (-4 * 2 + -4x * 2 + 12y * 2) = 0 (-8 + -8x + 24y) = 0 Solving -8 + -8x + 24y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + -8x + 8 + 24y = 0 + 8 Reorder the terms: -8 + 8 + -8x + 24y = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -8x + 24y = 0 + 8 -8x + 24y = 0 + 8 Combine like terms: 0 + 8 = 8 -8x + 24y = 8 Add '-24y' to each side of the equation. -8x + 24y + -24y = 8 + -24y Combine like terms: 24y + -24y = 0 -8x + 0 = 8 + -24y -8x = 8 + -24y Divide each side by '-8'. x = -1 + 3y Simplifying x = -1 + 3y
| h^2+6h-23=0 | | 3x+15=45+x | | 20x+30=180 | | (3x-4x+2y)*(2y+3y+2x)= | | -2x-5(x+1)=-x | | 6e^3x=30 | | 11[5-(4-2x)]+10x=4(8x+4)-5 | | w(26)=3x-1 | | xFactor+3x+2=0 | | y=.5x+-19 | | 5x-36=34+4x | | 5x+4(x-2)=10x+6 | | -2x+5x-14=3(x-1)-26 | | 1.2(b-12)=84 | | g=8y-m/y | | -x-2=-3x-5 | | 0.6x+14.8=x-1.56 | | 331.11=9(0.08m+26.90+0.10(26.90)) | | x^3-1/4x^2-2x-3=0 | | 6x+6.4=2(4x-2.8) | | 245=70+t | | 3(2x+7)=5x+17+x | | 2q+457=875 | | [(x-10)-24]+(x-10)+x=180 | | 8x+3-10=-2(x-2)+3 | | -3(t-2)+8t=7t-4 | | 4t+13b=487 | | 0.2x+0.5=-0.1 | | -24+x=x+11 | | 5(y-8)/3=-4y | | 3(x-4.3)=3.6 | | 6/10-4/10 |